British Journal of Biomedical Science in 2017: What have we learned?. Issue 1 (2nd January 2018) - Blann, Andrew
Abstract: In 2017 the British Journal of Biomedical Science published 35 articles in the various disciplines that comprise biomedical science. These were 6 reviews, 22 original articles, 6 'In Brief' short reports and one guideline. Of these, the majority were in clinical chemistry (one review, six data papers), microbiology (one review, four data papers), cellular pathology (four data papers) and virology (one review, two data papers). There were two data papers in transfusion science, whilst haematology, cytopathology and immunology were each represented by one review and one data paper. Reflecting the increasing complexity of the laboratory, five data papers crossed barriers between traditional disciplines, and so may be described as multidisciplinary. The present report will summarise key aspects of these publications.